Formation of the culture of economic thinking of future teachers of geography as a pedagogical problem (Pedagogy of Higher and Secondary Education, 2011)
The problem of formation of Geography teachers-to-be economic thinking culture is considered in the paper. The author on various approaches to defining the terms “economic thinking” and “economic culture”.
Keywords: economic thinking; economic culture